Determinants Of Commercial Bank Profitability In Malaysia - K. Guru, Balachandher; J. Staunton, J. Staunton; B. Shanmugam, B. Shanmugam (Asian Academy of Management (AAM), 2000)
Why are some commercial banks more successful than others? To what extent, are the profitability performance disparities due to variations in management controllable internal factors and to what extent; do environment related external factors influence the profitability performance of these institutions? This research paper was initiated by a series of questions such as these. It attempts to identify the determinants of successful commercial banks in order to provide practical guides for improved profitability performance of these institutions.